Dynamics of Population Savings in Russia and Foreign Countries: Estimation and Forecast - N. M. Yartseva; N. V. Sedova (Вестник Российского экономического университета имени Г. В. Плеханова, 2024)
In conditions of geo-political instability in the Russian Federation the necessity to raise standard of living of the population became evident, thus it is needed to forecast dynamics of population savings, which is important for strategic decision-making on the federal level. In order to analyze and forecast the total volume of savings of the Russian population the authors worked out a system of factors that influence the object of forecasting. On the basis of factor analysis they elaborated scenario forecast of dynamics of savings of the population in the country and dynamics of consumer spending up to 2025, including basic, conservative and target variants of the forecast. The present research confirms the thesis of interaction between unstable economic situation and arising of barriers for savings, at the same time it demonstrates a number of current and future problems caused by economic uncertainty. The authors proposed steps aimed at elimination of negative trends in dynamics of population savings in Russia.